YangXue QingNao Wan and Silibinin Capsules, the Two Chinese Medicines, Attenuate Cognitive Impairment in Aged LDLR (+/-) Golden Syrian Hamsters Involving Protection of Blood Brain Barrier - Gu, You-Yu; Huang, Ping; Li, Quan; Liu, Yu-Ying; Liu, George; Wang, Yu-Hui; Yi, Ming; Yan, Li; Wei, Xiao-Hong; Yang, Lei; Hu, Bai-He; Zhao, Xin-Rong; et al. (Frontiers in Physiology, 2018)
The purpose of the study was to explore the effect and the underlying mechanism of YangXue QingNao Wan (YXQNW) and Silibinin Capsules (SC), the two Chinese medicines, on cognitive impairment in older people with familial hyperlipidaemia. Fourteen month-old female LDLR (+/-) golden Syrian hamsters were used with their wild type as control. YXQNW (0.5g/kg/day), SC (0.1g/kg/day) or YXQNW (0.5g/kg/day) + SC (0.1g/kg/day) were administrated orally for 30 days. To assess the effects of the two drugs on plasma lipid content and cognitive ability, plasma TC, TG, LDL-C, and HDL-C were measured, and Y maze task was carried out both before and after administration. After administering of the drugs for 30 days, to evaluate the effect of the two drugs on disturbed blood flow caused by hyperlipedemia, the cerebral blood flow (CBF) was measured. To assess blood brain barrier integrity, albumin leakage in middle cerebral artery (MCA) area was determined. To evaluate the effect of the drugs on impaired microvessels, the number and morphology of microvessels were assessed in hippocampus area. To further evaluate the ultrastructure of microvessels in hippocampus, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were carried out. To assess the profiles of claudin-5 and occludin in hippocampus, we performed immunofluorescence. Finally, to assess the expression of claudin-5, JAM-1, occludin and ZO-1 in hippocampus, western blot was carried out. The results showed that YXQNW, SC and YXQNW + SC improved cognitive impairment of aged LDLR (+/-) golden Syrian hamsters without lowering plasma TC and LDL-C. YXQNW, SC and YXQNW + SC attenuated albumin leakage in MCA area and neuronal damage in hippocampus, concomitant with an increase in CBF, a decrease of perivascular edema and an up-regulated expression of claudin-5, occludin and ZO-1. In conclusion, YXQNW, SC and YXQNW + SC are able to improve cognitive ability in aged LDLR (+/-)golden Syrian hamsters via mechanisms involving maintaining blood brain barrier integrity. These findings provide evidence suggesting YXQNW or SC as a potential regime to counteract the cognitive impairment caused by familial hypercholesterolemia.